The Critical Role of Awake Brain Mapping in Glioma Surgery - Bhandari, Dilip; Pant, Basant; Fujii, Masazumi (Nepal Journal of Neuroscience, 2024)
Gliomas are among the most challenging brain tumors to manage due to their infiltrative nature and frequent proximity to eloquent brain regions responsible for speech, motor, and cognitive functions. The primary goal of glioma surgery is to achieve maximal safe resection, a delicate balance between achieving extensive tumor removal and preserving critical neurological functions. Awake brain mapping has emerged as a transformative approach, enabling surgeons to delineate functional brain areas in real-time and enhancing patient outcomes.